2011
DOI: 10.1002/ibd.21533
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of computed tomography enterography and magnetic resonance enterography for assessment of disease activity and complications in ileocolonic Crohnʼs disease

Abstract: MR and CT are equally accurate to assess disease activity and bowel damage in CD. MR may be superior to CT in detecting intestinal strictures and ileal wall enhancement. MR may represent an alternative technique to CT in assessing ileocolonic CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(163 citation statements)
references
References 36 publications
4
148
1
10
Order By: Relevance
“…MRE is very precise in determining the location and extension of the inflammatory lesions (sensitivity 74%, specificity 91%) in CD (5), which is very close to the precision demonstrated by CT enterography (18) and greater than the precision of ultrasound for locations in the jejunum and proximal ileum (19). In our series, the majority of the patients in whom an extension study was performed using MRE, disease activity was found in the jejunum and proximal ileum which led to a change in the therapeutic management of these patients due to having extensive disease.…”
Section: Discussionsupporting
confidence: 55%
“…MRE is very precise in determining the location and extension of the inflammatory lesions (sensitivity 74%, specificity 91%) in CD (5), which is very close to the precision demonstrated by CT enterography (18) and greater than the precision of ultrasound for locations in the jejunum and proximal ileum (19). In our series, the majority of the patients in whom an extension study was performed using MRE, disease activity was found in the jejunum and proximal ileum which led to a change in the therapeutic management of these patients due to having extensive disease.…”
Section: Discussionsupporting
confidence: 55%
“…US accuracy lower for disease proximal to terminal ileum US, CT, MRI all high accuracy for detection of fistulas, abscesses, stenosis. US higher false positive for abscesses Fiorino et al [43] , MRE significantly superior to CTE in detecting internal strictures: sensitivity (92% vs 85%), accuracy (95% vs 91%), specificity (90% vs 51%) Overall no significant difference in sensitivity and specificity of MRE and CTE in localising CD, bowel wall thickening, bowel wall enhancement, enteroenteric fistulas, detection of abdominal nodes, perivisceral fat enhancement Per segment analysis, MRE significantly superior to CTE in detecting ileal wall enhancement, with higher sensitivity (93% vs 81%) and accuracy (88% vs 81%), but lower specificity (72% vs 81%). MRE significantly superior in localising rectal disease, with higher accuracy (93% vs 85%), specificity (100% vs 50,9%) but lower sensitivity (72% vs 81%)…”
Section: Conventional Ct Mrementioning
confidence: 99%
“…MRE provides superior soft tissue contrast resolution compared to CTE, allowing detailed visualisation of inflammatory and fibrotic bowel wall [42] . A 2011 Italian prospective study by fiorino et al [43] compared MRE and CTE in 44 patients with ileocolonic CD. They found comparable accuracy between MRE and CTE in localising CD, assessing bowel wall thickening, bowel wall enhancement and enteroenteric fistula.…”
Section: Mrementioning
confidence: 99%
“…Pesquisas recentes demonstraram uma precisão comparável entre RNM e TC na avaliação do espessamento da parede intestinal, aumento da parede e fístula enteroentérica. Contudo, a RNM foi superior a TC na detecção de estenoses e aumento da parede ileal (FIORINO et al, 2011).…”
Section: Ressonância Nuclear Magnéticaunclassified